2009
DOI: 10.1108/01437730910961658
|View full text |Cite
|
Sign up to set email alerts
|

Leadership‐shaping experiences: a comparative study of leaders and non‐leaders

Abstract: Purpose -By comparing "leaders" with "non-leaders" the current research attempts to shed light on the impact of early experiences on leaders' development. Design/methodology/approach -The study is presented in two parts, quantitative and qualitative. In the first (quantitative) part, a group of soldiers perceived as leaders was compared with a group of soldiers perceived as non-leaders, in order to examine the hypothesis that leaders have had more leadership experiences than non-leaders. Confirmation of this h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
1
13
1
Order By: Relevance
“…Self-report measures have been shown to be a reliable way of measuring leader self-perception, with several studies demonstrating their predictive validity. For example, selfreports of leadership self-perception have been found to be predictive of the amount of leadership experiences individuals had during their youth (Amit, Popper, Gal, Mamane-Levy, & Lisak, 2009), leadership self-efficacy (Van der Mescht, 2004), and attitude toward leadership and leadership emergence (Kolb, 1999).…”
mentioning
confidence: 99%
“…Self-report measures have been shown to be a reliable way of measuring leader self-perception, with several studies demonstrating their predictive validity. For example, selfreports of leadership self-perception have been found to be predictive of the amount of leadership experiences individuals had during their youth (Amit, Popper, Gal, Mamane-Levy, & Lisak, 2009), leadership self-efficacy (Van der Mescht, 2004), and attitude toward leadership and leadership emergence (Kolb, 1999).…”
mentioning
confidence: 99%
“…In addition, this study also wants to understand the role of LSE in mediating the relationship between Past Leadership Experiences (PLE) and AI-MTL and between Perceived Job Stress as an Academic Leader and AI-MTL. Basing their views on Bandura's theory, Amit et al (2009) suggest that LSE mediates the relationship between past leadership experiences and AI-MTL. This is because past successful experiences are believed to increase someone's selfconfidence as a leader, which further increase his/her desire to take leadership positions (AI-MTL).…”
Section: Lse As a Mediatormentioning
confidence: 99%
“…Past Leadership Experiences are also believed to boost someone's leadership skills (Bergner et al, 2018). Previous leadership roles are believed to form person's self-image as a leader and thus motivate him/her to take on a similar role in the future (Amit et al, 2009). Considering Chan and Drasgow's (2001) suggestion regarding the need to pay attention to organizational context in MTL, the researchers add two other factors that allegedly will also affect AI-MTL.…”
Section: Introductionmentioning
confidence: 99%
“…It's those beliefs and assumptions that drive their current behavior' (cited in Lee, 1989: 21). Research studies carried out by Kempster (2006) as well as Amit et al (2009) found that those who emerge as leaders proved to have had more leadership experiences in their youth, and that these experiences helped shaped their self-perception as leaders.…”
Section: Leadership Program Emphasismentioning
confidence: 99%